PENERAPAN MODEL SOLE BERBANTUAN WHATSAPP DAN PROJECT WORK PADA MASA PANDEMI COVID-19 - MUHTAR MUHTAR (Direktorat Guru dan Tenaga Kependidikan Pendidikan Menengah dan Pendidikan Khusus, 2021)
The covid-19 pandemic has an impact on face-to-face lerning in class to learning from home using online and/or offline methods. The research aims to determine the implementation of learning through WhatsApp media, apply the SOLE (self organized learning environmant) methode in learning and carry out learning with project work in class X SMKN 6 Palu. Primary data were obtained from students' responses through written tests and secondary data from online and offline assigment portofolios. Activities using WhatsApp media include group division, task information, disciussions, tecnical guidance/steps for completing tasks and sharing relevant learning resource links, the SOLE model is implemented by implementing stimulation question steps, group division, investigation, monitoring, presentation, and evaluation/reflection. Offline learning with projects following preparation, implementation, and results. The results show that the application of the SOLE model assisted by WhatsApp media encourages students to learn actively so that learning objectives are achieved, SOLE models develop higher-order thinking, task completion strategis, and dept of learner knowledge and project learning, enhacing dicipline, coorporation, responsibility, and performance aspects of learners.